Linear decline in red snapper (Lutjanus campechanus) otolith Δ14C extends the utility of the bomb radiocarbon chronometer for fish age validation in the Northern Gulf of Mexico. (3rd May 2018) - Barnett, Beverly K; Thornton, Laura; Allman, Robert; Chanton, Jeffrey P; Patterson, William F
Abstract: Radiocarbon (Δ 14 C) was analyzed in northern Gulf of Mexico (nGOM) red snapper ( Lutjanus campechanus ) otolith cores ( n = 23), otolith edge samples ( n = 12), and whole age-0 otoliths ( n = 9), with edge samples and whole age-0 otoliths constituting known-age samples. There was no significant difference in the linear relationship of Δ 14 C versus year of formation between regional corals and known-age otolith samples, and a linear regression fit to the combined data from 1980 to 2015 extends the utility of the bomb radiocarbon chronometer for age validation. The entire regional coral and known-age otolith data set (1940 to 2015) was then utilized as a reference series to validate otolith-derived red snapper age estimates for cored otolith samples. A loess regression was fit to the reference data and then the sum of squared residuals (SSR) was computed from predicted versus observed birth years for cored adult otolith samples. This process was then repeated for ages biased ±1–4 years. Ages with no bias applied had the lowest SSR, thus validating red snapper age estimates and demonstrating the utility of the combined regional coral and known-age red snapper otolith Δ 14 C time series for age validation of nGOM marine fishes.